Developmental Changes in ERP Responses to Spatial Frequencies - van den Boomen, Carlijn; Jonkman, Lisa M.; Jaspers-Vlamings, Petra H. J. M.; Cousijn, Janna; Kemner, Chantal (PLOS ONE, 2015)
Social interaction starts with perception of other persons. One of the first steps in perception is processing of basic information such as spatial frequencies (SF), which represent details and global information. However, although behavioural perception of SF is well investigated, the developmental trajectory of the temporal characteristics of SF processing is not yet well understood. The speed of processing of this basic visual information is crucial, as it determines the speed and possibly accuracy of subsequent visual and social processes. The current study investigated developmental changes in the temporal characteristics of selective processing of high SF (HSF; details) versus low SF (LSF; global). To this end, brain activity was measured using EEG in 108 children aged 3–15 years, while HSF or LSF grating stimuli were presented. Interest was in the temporal characteristics of brain activity related to LSF and HSF processing, specifically at early (N80) or later (P1 or N2) peaks in brain activity. Analyses revealed that from 7–8 years onwards HSF but not LSF stimuli evoked an N80 peak. In younger children, aged 3–8 years, the visual manipulation mainly affected the visual N2 peak. Selective processing of HSF versus LSF thus occurs at a rather late time-point (N2 peak) in young children. Although behavioural research previously showed that 3–6 year-olds can perceive detailed information, the current results point out that selective processing of HSF versus LSF is still delayed in these children. The delayed processing in younger children could impede the use of LSF and HSF for emotional face processing. Thus, the current study is a starting point for understanding changes in basic visual processing which underlie social development.